Re-evaluation of the PBAN receptor (PBANR) molecule: characterization of PBANR variants expressed in the pheromone glands of moths - Lee, Jae M.; Hull, J. J.; Kawai, Takeshi; Goto, Chie; Kurihara, Masaaki; Tanokura, Masaru; Nagata, Koji; Nagasawa, Hiromichi; Matsumoto, Shogo (Frontiers in Endocrinology, 2012)
Sex pheromone production in most moths is initiated following pheromone biosynthesis activating neuropeptide receptor (PBANR) activation. PBANR was initially cloned from pheromone glands (PGs) of Helicoverpa zea and Bombyx mori. The B. mori PBANR is characterized by a relatively long C-terminus that is essential for ligand-induced internalization, whereas the H. zea PBANR has a shorter C-terminus that lacks features present in the B. mori PBANR critical for internalization. Multiple PBANRs have been reported to be concurrently expressed in the larval CNS of Heliothis virescens. In the current study, we sought to examine the prevalence of multiple PBANRs in the PGs of three moths and to ascertain their potential functional relevance. Multiple PBANR variants (As, A, B, and C) were cloned from the PGs of all species examined with PBANR-C the most highly expressed. Alternative splicing of the C-terminal coding sequence of the PBAN gene gives rise to the variants, which are distinguishable only by the length and composition of their respective C-terminal tails. Transient expression of fluorescent PBANR chimeras in insect cells revealed that PBANR-B and PBANR-C localized exclusively to the cell surface while PBANR-As and PBANR-A exhibited varying degrees of cytosolic localization. Similarly, only the PBANR-B and PBANR-C variants underwent ligand-induced internalization. Taken together, our results suggest that PBANR-C is the principal receptor molecule involved in PBAN signaling regardless of moth species. The high GC content of the C-terminal coding sequence in the B and C variants, which makes amplification using conventional polymerases difficult, likely accounts for previous “preferential” amplification of PBANR-A like receptors from other species.